PIP5K1A Suppresses Ferroptosis and Induces Sorafenib Resistance by Stabilizing NRF2 in Hepatocellular Carcinoma - Mengzhou Guo; Sinuo Chen; Jialei Sun; Ruchen Xu; Zhuoran Qi; Jie Li; Lianer Zhou; Yuan Fang; Tianshu Liu; Jinglin Xia (Advanced Science)
Abstract Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related mortality worldwide. Ferroptosis, an iron‐dependent form of programmed cell death driven by lipid peroxidation, has emerged as a promising strategy for cancer treatment. However, the development of ferroptosis resistance limits the efficacy of such treatments. This study reports that phosphatidylinositol 4‐phosphate 5‐kinase 1 alpha (PIP5K1A) promotes HCC tumorigenesis and predicts poor prognosis in HCC patients. Knockdown of PIP5K1A enhances lipid peroxidation and increases sensitivity to sorafenib‐induced ferroptosis by inhibiting the activation of downstream ferroptosis‐related genes regulated by nuclear factor erythroid‐2‐related factor 2 (NRF2). Mechanistically, PIP5K1A competitively binds to the Kelch domain of Kelch‐like ECH‐associated protein 1 in a kinase‐independent manner, leading to NRF2 escaping from ubiquitination degradation, thereby promoting NRF2‐dependent transcription and suppressing ferroptosis. Furthermore, ISA‐2011B, a PIP5K1A‐specific inhibitor, effectively inhibits HCC growth and sensitized HCC cells to sorafenib. In conclusion, PIP5K1A is a promising therapeutic target for improving the efficacy of sorafenib and other ferroptosis inducers in HCC.